Traumatic brain injuries in children: a hospital-based study in Nigeria (2013)
Background: Traumatic Brain Injury (TBI) is a significant cause of morbidity and mortality worldwide. Our previous studies showed a high frequency of motor vehicle accidents among neurosurgical patients. However, there is a dearth of data on head injuries in children in Nigeria. Aims: To determine the epidemiology of paediatric traumatic brain injuries. Setting and Design: This is a prospective analysis of paediatric head trauma at the University of Benin Teaching Hospital, a major referral centre for all traumatic brain injuries in Nigeria between October 2006 and September 2011. Materials and Methods: We studied the demographic, clinical and radiological data and treatment outcomes. Data was analysed using statistical package for the social sciences (SPSS) 16.0. Results: We managed 127 cases of paediatric head injuries, 65 boys and 62 girls representing 13% of all head injuries managed over the 5-year period. They were aged 3 months to 17 years. The mean age was 7.4 years (median 7 years) with peak incidence occurring at 6-8 years i.e. 31 (24.4%) cases. Motor vehicle accidents resulted in 67.7%, falls 14% and violence 7%. The most frequent computed tomography finding was intracerebral haemorrhage. Mean duration of hospitalization was 18 days (median 11 days). Eleven patients died, mortality correlating well with severity and the presence of intracerebral haematoma. Conclusion: Head injuries in children are due to motor vehicle and motor vehicle-related accidents. Hence, rational priorities for prevention of head injuries in children should include prevention of vehicular, especially pedestrian, accidents in developing countries